lbn Sina and Mysticism (American Journal of Islam and Society, 1998)
S. Inati, translator. Ibn Sina and Mysticism: Remarks and Admonitions(Al-Isharat wa al-Tanbihat), Part Four. London and New York: KeganPaul International, 1996, pp. 114. The book is an Fhglish translation andanalysis of the fourth part of Ibn Sina’s Al-Isharat wa al-Tanbihat.This book “announces” a contribution to a specific aspect of Ibn Sina’sthought. Its main focus is the fourth part of his Al-Isharat wa al-Tanbihat(Remarks and Admonitions), which deals in a systematic manner withIslamic Sufism (mysticism), its different modifcations, and the kind ofternpod and transcendental experience that the soul undergoes in itsjourney back to its origin. Dr. S. Inati’s translation is the first into Englishof this part of the Isharat.’ It includes Ibn Sina’s dissertation in which heemploys a form of descriptive psychology and scant aspects of his metaphysicalsystem, as a focal point, to explain the drama of mystical life,its actualities, horizons, and pretensions. The Archimedean point of theIsharat is the experience of the Sufi (mystic) described in a crisp, vivid,and resonant Arabic. There is an excited, dynamic, and luminous simplicityin his style with sparse metaphors and practically no symbols orenigmas to hinder a direct comprehension of the themes discussed therein.Dr. Inati’s position on the Isharat is in harmony with the popularlyheld beliep that it is entirely a symbolic composition (pp. 2-3) whichstands for or represents his othewise clear naturalistic doctrine? I disagreeand shall defend this position later. The best part of this work isdirectly communicated, employing his conceptual categories as a deviceto illuminate the process of mystical gnosis. He must have believed thatan appeal to his rational determinations from his cosmology and theoryof the soul would provide models or “ideated structures” that enhance abetter understanding of mysticism by himself and by his competent der.The Shaykh’s contribution in Isharut lies in his methd of descriptionand inteptation and not in major novel themes about mysticism; the ...